Cover crop usage for the sustainable management of soilborne diseases in woody ornamental nursery production system. Issue 3 (4th May 2022) - Parajuli, Madhav; Panth, Milan; Gonzalez, Axel; Addesso, Karla M.; Witcher, Anthony; Simmons, Terri; Baysal-Gurel, Fulya
Abstract: Cover crops represent a potential tool for suppression of soil borne diseases in woody ornamental nursery production, which can cause significant economic losses. Field experiments were conducted in 2019 and 2020 to explore the effects of a cover crop and the timing of cover crop disturbance on soilborne disease suppression. Soils from red maple ( Acer rubrum 'October Glory ') plantations grown with or without a cover crop [crimson clover ( Trifolium incarnatum )] were sampled following senescence of the cover crop. Greenhouse bioassays were conducted using red maple cuttings on inoculated (with Rhizoctonia solani, Phytopythium vexans or Phytophthora nicotianae ) and non-inoculated field soils. Plant height, total and root fresh weight were measured, and the roots were assessed for disease severity on a 0 to 100% root damage scale. Pathogen recovery was assessed by culturing root pieces (~1 cm length) on oomycetes or Rhizoctonia semi-selective media. Soil samples were analyzed for organic matter, nitrogen, phosphorus, potassium, pH and Pseudomonad population count. A minimal effect of cover crop disturbance timing (late fall or early spring) was found on disease suppression. Cover crop usage reduced disease severity and pathogen recovery in red maple field soils. Plants grown in cover cropped soil had greater total, root and aboveground fresh weight compared with those from non-cover cropped soil, but plant height was not affected. Cover crops increased soil organic matter and total nitrogen in 2020. Pseudomonad populations were higher when cover crops were used. The results suggest that cover crops can reduce soilborne disease in woody ornamentals.